The more the better? The non-linear effect of workload on workplace well-being - Liang, Juan; Zhou, Wenxin; Xu, Bibo; Jiang, Hai (Frontiers in Psychology, 2026)
IntroductionIt is unclear what level of workload is best for workplace well-being, in part because researchers have only tested linear relationships. We tested an inverted U-shaped model in which workplace well-being is optimal at a moderate level of workload. The mediation effect of autonomous motivation were also tested.MethodsWe conducted two studies with employees. Study 1 (N = 324) used a cross-sectional survey design and was analyzed using SPSS20.0. Study 2 (N = 152) used experience sampling methodology and was analyzed using Mplus8.3. The data were analyzed using non-linear analytical techniques and mediation analyses conducted with the PROCESS macro.ResultsThe data were analyzed using non-linear analytical techniques and mediation analyses conducted with the PROCESS macro. The results of both studies showed a U-shaped curve, but contrary to expectations, the curve was positive rather than inverted: an increase in workload from low to moderate was associated with decreased workplace well-being, but an increase in workload from moderate to high was associated with increased workplace well-being. The mediation effect of autonomous motivation emerged in study 1, but not Study 2.DiscussionThese results suggest that employees should be given a moderate workload that can be increased, rather than starting with a low workload.